Investigating Factors Affecting Students’ Attitudes and Readiness Towards Collaborative Online Learning Environments in Physics - Ardian Asyhari; Happy Komikesari (CV FOUNDAE, 2024)
education, yet many students face challenges in adapting to its demands. This study explores factors influencing students’ readiness for collaborative online learning, focusing on prior knowledge, motivation, technological proficiency, and learning preferences. A mixed-methods approach was used to collect quantitative data from 45 students, which were analyzed using SEM-PLS, along with qualitative insights from focus group discussions. Results identified prior knowledge as the strongest predictor of readiness (B = 0.670, p = 0.001), enhancing cognitive engagement and motivation. Motivation influenced learning preferences (B = 0.482, p = 0.009) but did not directly impact readiness. Technological proficiency moderately predicted readiness (B = 0.353, p = 0.057), while learning preferences were nonsignificant (B = 0.218, p = 0.421). Qualitative findings emphasized the role of peer collaboration, intrinsic motivation, and digital skill disparities. The study highlights the need for scaffolding prior knowledge, fostering motivation through structured tasks, improving digital skills, and offering strategies for creating inclusive and effective collaborative online learning environments.